Erratum to: Prevalence of methicillin-resistant Staphylococcus aureus carriage on admission among patients attending regional hospitals in Dar es Salaam, Tanzania - Agricola Joachim; Sabrina J. Moyo; Lillian Nkinda; Mtebe Majigo; Elia Mmbaga; Naboth Mbembati; Said Aboud; Eligius F. Lyamuya (BMC Research Notes, 2017)
Following publication of the original article [1], author Elia Mmbaga pointed out that her name had been misspelt as Elia Mbaga.